STUDY OF THE CHARACTERISTICS OF THE USE OF STREET VENDORS' ROOMS (PKL) IN THE DEPARTMENT OF INDUSTRY AND TRADE IN THE FIELD OF MARKET MANAGEMENT OF SUNGAI PENUH CITY: AFRIYANTI - AFRIANTI, SE., M.Pd (LPPM STIA Nusantara Sakti, 2022)
Characteristics of the Street Vendors Usage in Sungai Penuh City. Management Office The formulation of research problem. How the Characteristics Study of the Useof Street Vendors’ Spatial Planning in Sungai Penuh City? This study uses a qualitative approach in which data obtained through free field interviews with 9 informant. From the results of the study note that the Characteristics of Use of Spatial Street Vendors in Sungai Penuh City. Traders are not fully aware that trading on roadside and sidewalks w3ill damage the beauty of the city.The street vendors in Sungai Penuh City actually are also willing to relocate trading locations, but there problem is the absence of a suitable location trading location. Trough there conditions, the goverment can only safeguard public order and public order.